Application of SCOR flexibility metrics to assess the Industry 4.0-Readiness of Supply Chain Networks: An empirical study - Laura Reder; Timo Klünder (Ruhr-Universität Bochum, Lehrstuhl für Produktionswirtschaft, 2017)
The development of Industry 4.0 (I4.0) necessitates flexible Supply Chain Networks (SCN). Therefore, this paper assesses the flexibility of SCN in context of I4.0. The assessment is based on a framework of metrics embedded in the Supply Chain Operations Reference (SCOR) model. The methodology employed integrates the Analytical Hierarchy Process (AHP) and the Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE) to weight the selected SCOR indicators and to determine the SCN I4.0-Readiness. The computations are based on empirically tested SCOR-data and expert judgements. The developed I4.0-Readiness-Assessment tool reveals a lack of SCN's utilization of the full potential of I4.0.
Keywords: 650; Industry 4.0; Supply Chain Networks; Flexibility Assessment